Blended Learning and Project Based Learning: The Method to Improve Students’ Higher Order Thinking Skill (HOTS) - Rifda Eliyasni; Ary Kiswanto Kenedi; Inaad Mutlib Sayer (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
The background of this research was the demands of the industrial revolution 4.0 era. Hence, the students should have high-oder thinking skills and lecturers must be able to create learning that was able to achieve these demands. This study examined the effect of Blended Learning and Project Based Learning in improving the students’ Higher Order Thinking Skill (HOTS). This research was an experimental research with a quasi-experiment design type. The sample of this research was 90 students from Primary School Teacher Education Department at State University of Padang. This research proven that the obtained t count = 4.374 with df = 392.24 and sig (1 way) = 0.000 where sig (1 way) <0.05. It concluded that there was an improving of students’ HOTS ability that learned using Blended Learning and Project Based Learning rather than of using Blended Learning only. This research of using Blende-Learning and Project Based learning could improve on students' higher-order thinking skills. This research implied using Blended Learning and Project Based learning model was an alternative to improve Higher Order Thinking Skill (HOTS). Keywords: Blended Learning, Higher Order Thinking Skill (HOTS), Project Based Learning.